Barriers Hindering Tribal Farm Women’s Access to Agri-Allied Information - Bahubalendra, Shilpa; Mishra, Bishnupriya; Jayasingh, Debi Kalyan; Anand, Ashish (Indian Journal of Extension Education, 2025)
Tribal farm women play a crucial role in agriculture, household maintenance, and resource management while upholding cultural and ecological practices. However, limited access to agricultural information impedes inclusive development. To examine these challenges, an ex-post facto study was conducted in Odisha to identify the constraints they encountered. A sample of 240 respondents from two districts was selected through multi-stage random sampling, with data collected via semi-structured interviews. Key socio-personal issues included dominance of domestic work (63.55) and increased drudgery (56.63). Under extension and training, lack of resources (62.97) and unsuitable programme timing (59.41) were prominent. Marketing challenges involved distant markets (72.53) and poor transport (56.44), while communication barriers included high cost (73.24) and tool usability issues (59.39). Tackling these challenges through a holistic, solution-focused approach is essential to improve tribal women farmers' access to agricultural information and enhance their overall informational reach.